Peran Pendidikan Kewarganegaraan dalam Membentuk Karakter Multikultural Siswa - Bakar, Abu (Sekolah Tinggi Ilmu Tarbiyah Al- Kifayah Riau, 2022)
This study aims to describe the role of Civic Education in shaping the multicultural character of elementary school students. The research method used is library research with a qualitative approach. The subjects of this study are theories and previous relevant studies, while the objects are the concepts of Civic Education and the multicultural character of elementary students. Data collection techniques include document studies and scholarly literature, while data analysis was conducted using content analysis and thematic synthesis. The results show that Civic Education plays a crucial role in instilling values of tolerance, appreciation of diversity, and harmonious living in a pluralistic society. Through the integration of multicultural approaches in the curriculum, learning methods, and the role of teachers and school environment, students’ multicultural character can be developed optimally. The conclusion confirms that Civic Education serves as a strategic instrument in educating inclusive, democratic, and diversity-appreciating future generations.